STRATEGI PENANGGULANGAN HIV DAN AIDS DI KOTA SEMARANG - Kristanto, Tri Wahyu; Mustam, M.; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
HIV (Human Immunodeficiency Virus) is the virus that causes AIDS (Acquired Immunodeficiency Syndrome) is a set of symptoms that arise due the decline in immunity. Semarang city as the capital city of Central Java province has the tendencies detection rate of HIV and AIDS cases that are increasing every year. Various programs have been implemented so far, but the results still have not seen due to several influence factors. This study uses descriptive qualitative research methods to describe the situation of HIV and AIDS in the city of Semarang.There are several driving factors on the implementation of the program and the strategy are: the suitability of the vision and mission, the quality of human resources, factors conducive political, regulatory support, economic growth, as well as the use of technology. While the inhibiting factors, among others: the lack of budget, the absorption of financial resources less effective, negative stigma against people living with HIV, and the adverse effects of technology (pornography).After analyzing these factors, it has produced some of the recommendation in the response to HIV and AIDS in the city, which are: make strategic planning, improve coordination with NGOs and people living with HIV, involving the private sector and community participation in each program and activity, providing sex education for young people both within schools, colleges, and Karang Taruna.